Plants in the Qur'an and Hadith: A Thematic Study on Ecological Values in Islamic Perspective - Lisa Karunia; Aulia Pravaita Hapsari J.M; Alihan Satra (Jurnal Riset Pendidikan Multidisiplin dan Pengabdian Kepada Masyarakat, 2026)
Plants are one of the creations of Allah SWT that play an important role in maintaining the balance of life on Earth. The Qur'an and the hadiths of Prophet Muhammad SAW extensively discuss the creation, functions, and virtues of caring for plants as part of humanity’s responsibility as khalifah (stewards) on Earth. This article aims to examine Qur'anic verses and hadiths related to plants and connect them with the perspective of modern science. The method used in this study is library research with a qualitative descriptive approach through the analysis of Islamic sources and scientific references. The results of the study show that plants were created in balance and possess highly vital ecological functions as providers of oxygen, sources of food, regulators of the water cycle, and maintainers of ecosystem stability. In addition, the Qur'an uses plants as philosophical metaphors to describe the quality of human faith and deeds.